Circulating Dendritic Cells from Celiac Disease Patients Display a Gut‐Homing Profile and are Differentially Modulated by Different Gliadin‐Derived Peptides. Issue 6 (5th February 2020) - Escudero‐Hernández, Celia; Martín, Álvaro; de Pedro Andrés, Rodrigo; Fernández‐Salazar, Luis; Garrote, José Antonio; Bernardo, David; Arranz, Eduardo
Abstract : Scope: Circulating dendritic cell (DC) and monocyte subsets contribute to the pool of intestinal DC and macrophages in celiac disease (CeD), an autoimmune gut disorder triggered by dietary gluten. Here, this study aims to characterize these circulating subsets in CeD and assess the effect of different gliadin‐derived peptides on conventional DC (cDC). Methods and results: Flow cytometry profiling of peripheral blood mononuclear cells reveals a slight decrease in the proportion of plasmacytoid and type 1 cDC in gluten‐free diet (GFD)‐treated CeD patients. In comparison to healthy donors, DC and monocyte subsets from active and GFD‐treated CeD patients display an increased gut‐homing profile. Type 2 cDC (cDC2) are sorted and stimulated with the gliadin‐derived peptides 8‐mer, 19‐mer, and 33‐mer. All peptides induce cDC2 maturation, although the profile is different. While peptide 8‐mer induces a Th1/Th17 pro‐inflammatory cytokine profile in active CeD patients, cDC2 primed with peptide 33‐mer displays a higher capacity to promote gut‐homing CCR9 + expression onto autologous T‐cells. Conclusion: Distinct gliadin‐derived peptides elicit different effects on cDC2 phenotype and function. This effect is compatible with a model where diverse gliadin peptides may cooperate to promote full cDC2 activation and the subsequent T‐cell response in genetically predisposed individuals. Abstract : Gliadin‐derived peptides (i.e., 8‐mer, 19‐mer, and 33‐mer) may cooperate to promote full dendritic cell activation to develop a subsequent T‐cell response in genetically predisposed individuals (HLA‐DQ2 + )